Complementary feeding practices and nutritional status in infants living in Turkey: Iowa infant feeding attitude scale and complementary feeding index - Bilge Meral Koc; Tugce Ozlu Karahan; Ezgi Arslan Yuksel; Gokcen Garipoglu (Maternal and Child Nutrition)
Abstract Although complementary feeding (CF) and maternal attitudes towards infant feeding are known to affect the nutritional status of infants during the neonatal period, studies in this field remain limited. The present study aimed to determine CF practices for infants aged 6–12 months who live in Turkey and maternal attitudes towards infant feeding. In addition, the effects of CF practices and maternal attitudes on the nutritional status of infants were examined. This study included 720 infants, of whom 289 were aged 6–8 months and 431 were aged 9–12 months. CF status was assessed using the CF index (CFI), and maternal attitudes towards infant feeding were measured using the Iowa infant feeding attitude scale (IIFAS). The weight and length measurements of infants were categorized using z‐scores. Infants with weight‐for‐age z‐score (WAZ) and weight‐for‐length z‐score (WLZ) of less than −2 standard deviation were categorized as malnourished. Mothers of malnourished infants were found to have lower CFI and IIFAS scores (p < 0.05). Consistency of fruit feeding and complementary foods in the first 3 days of CF was associated with WAZ. The mothers' level of knowledge about CF and appropriate CF practices significantly affects the nutritional status of infants. The tools used in the present study to monitor CF practices should be incorporated into public health programmes.